Psycholinguistic Approach to Diagnostics and Modification of Individual Negative Core Beliefs - Zasiekina, Larysa (East European Journal of Psycholinguistics, 2015)
Psycholinguistic approach to diagnostics and modification of individual negative core beliefs.  The present research provides the first evidence for psycholinguistics resources    in diagnostics and modification of individual negative core beliefs. The individual core beliefs are treated as a system of subjectively experienced feeling of conscious or unconscious nature which expresses the attitude of personality towards himself/ herself, the world and other people. The results of the study were conceptually replicated: Participants’ core beliefs of lack of love were significantly correlated with their core beliefs of rejection (r=0.929, p